Increasing the Brand Image of the Sweembath Tourism Area Towards a Tourism Village in Naga Sopa Village, Bandar Huluan District, Simalungun Regency - Ma'ruf, Ma'ruf Tafsin; Eva, Eva Sartini Bayu; Peni, Peni Patriani; Hariadi , Hariadi Susilo; Dardanila, Dardanila; Tugiman, Tugiman; Farida , Farida Ariani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Â The embossed icon (image) is a promotional media or an identity media of a specific geographic era, whether it is a unique writing or logo that has the aim of attracting the attention of those who see it to be interested and want to look back, they will return to visit the tourist area. making a raised letter icon (image) â€œâ€ SWEEMBATH 'and' NATURAL WATER EYES 'is a promotional media or media identity, a geographically distinctive name, the origin of the naming is a unique writing or logo which has the aim of attracting the attention of those who see it to be interested and want to look back, they and then return to visit the tourist area and understand the history of the pennant spring. Making large embossed letters to become the sweembath location icon is needed, especially in relation to further promotions that can attract tourist visits. The making of the writing icon will be made at the front gate of the tourist location. The making of the letter icon is proven to be a location for selfies of visitors who generally will display their tourism activities or activities through social media such as Instagram, Facebook, YouTube, and others. The making of these letters has an impact on the promotion of sweembath tourist areas which are expected to increase the number of tourist visits in the future. Measurement of visitor perceptions answers a high level of satisfaction. The number shows that the satisfactionlevel who answered very satisfied reached 90%, and 10% answered satisfied. This condition shows that the sweembath tourist location is in a very significant direction compared to the previous ones. Several stakeholders, such as village managers and sub-district officials, tended to show their surprise at the changes made by USU's LPPM to these tourist sites, which led to a much better image than before. The survey results show that further improvements are needed, especially in the aspect of providing representative prayer facilities (mushola) in these locations. Another very basic condition that requires improvement is road access to tourist sites. The Simalungun Regional Government should be able to repair and maintain roads to these tourist sites so that the economic improvement of the tourism village community in Naga Sopa Village is better. Some of the measurements that were originally going to be carried out were the measurement of the increase in the number of tourist visits after USU's LPPM-assisted village activities. This measurement is difficult to do considering the current conditions related to the Covid 19 pandemic, which The embossed icon (image) is a promotional media or an identity media of a specific geographic era, whether it is a unique writing or logo that has the aim of attracting the attention of those who see it to be interested and want to look back, they will return to visit the tourist area. making a raised letter icon (image) â€œâ€ SWEEMBATH 'and' NATURAL WATER EYES 'is a promotional media or media identity, a geographically distinctive name, the origin of the naming is a unique writing or logo which has the aim of attracting the attention of those who see it to be interested and want to look back, they and then return to visit the tourist area and understand the history of the pennant spring. Making large embossed letters to become the sweembath location icon is needed, especially in relation to further promotions that can attract tourist visits. The making of the writing icon will be made at the front gate of the tourist location. The making of the letter icon is proven to be a location for selfies of visitors who generally will display their tourism activities or activities through social media such as Instagram, Facebook, YouTube, and others. The making of these letters has an impact on the promotion of sweembath tourist areas which are expected to increase the number of tourist visits in the future. Measurement of visitor perceptions answers a high level of satisfaction. The number shows that the satisfaction level who answered very satisfied reached 90%, and 10% answered satisfied. This condition shows that the sweembath tourist location is in a very significant direction compared to the previous ones. Several stakeholders, such as village managers and sub-district officials, tended to show their surprise at the changes made by USU's LPPM to these tourist sites, which led to a much better image than before. The survey results show that further improvements are needed, especially in the aspect of providing representative prayer facilities (mushola) in these locations. Another very basic condition that requires improvement is road access to tourist sites. The Simalungun Regional Government should be able to repair and maintain roads to these tourist sites so that the economic improvement of the tourism village community in Naga Sopa Village is better. Some of the measurements that were originally going to be carried out were the measurement of the increase in the number of tourist visits after USU's LPPM-assisted village activities. This measurement is difficult to do considering the current conditions related to the Covid 19 pandemic, which limits crowding activities in order to reduce the incidence of Covid 19 infection in the community, and the outcomes achieved, 1) mass media publications, 2) journals, 3) CD activities, and 4) documentary books activities